Synergistic Effects of Kartogenin and Transforming Growth Factor‐β3 on Chondrogenesis of Human Umbilical Cord Mesenchymal Stem Cells In Vitro. Issue 3 (28th May 2020) - Zhao, Yanhong; Teng, Binhong; Sun, Xun; Dong, Yunsheng; Wang, Shufang; Hu, Yongcheng; Wang, Zheng; Ma, Xinlong; Yang, Qiang
Abstract : Objective: To explore the effect of kartogenin (KGN) on proliferation and chondrogenic differentiation of human umbilical cord mesenchymal stem cells (hUCMSC) in vitro, and the synergistic effects of KGN and transforming growth factor (TGF)‐β3 on hUCMSC. Methods: Human umbilical cord mesenchymal stem cells were isolated and cultured. Then the differentiation properties were identified by flow cytometry analysis. HUCMSC were divided into four groups: control group, KGN group, TGF‐β3 group, and TK group (with TGF‐β3 and KGN added into the medium simultaneously). Cells in all groups were induced for 21 days using the suspension ball culture method. Hematoxylin and eosin, immunofluorescence, and Alcian blue staining were used to analyze chondrogenic differentiation. Real‐time reverse transcriptase polymerase chain reaction was performed to investigate genes associated with chondrogenic differentiation. Result: Hematoxylin and eosin staining showed that cells in the TGF‐β3 group and the TK group had formed cartilage‐like tissue after 21 days of culture. The results of immunofluorescence and Alcian blue staining showed that compared with the control group, cells in the KGN and TGF‐β3 groups demonstrated increased secretion of aggrecan after 21 days of culture. In addition, cells in the group combining KGN with TGF‐β3 (5.587 ± 0.27, P  < 0.01) had more collagen II secretion than cells in the TGF‐β3 alone group (2.86 ± 0.141, P  < 0.01) or the KGN group (1.203 ± 0.215, P  < 0.01). The expression of aggrecan (2.468 ± 0.097, P  < 0.05) and SRY‐Box 9 (4.08 ± 0.13, P  < 0.05) in cells in the group combining KGN with TGF‐β3 was significantly higher than those in the TGF‐β3 group (2.216 ± 0.09, 3.02 ± 0.132, P  < 0.05).' Conclusion: The combination of KGN and TGF‐β3 had synergistic effects and induced hUCMSC chondrogenesis. This could represent a new approach for clinical application and studies on cartilage repair and regeneration.